Intact and Impaired Mentalization and Its Relation to Empathy and Pain — a Cross-sectional Study of Patients with Opioid Use Disorder Receiving Methadone Maintenance Treatment. - Zorani, Shlomit; Peles, Einat (International Journal of Mental Health & Addiction, 2024)
We assessed the prevalence of normal theory of mind (ToM) in opioid use disorder patients receiving methadone maintenance treatment (MMT) and how it relates to chronic pain, pain empathy (PE), and pain sensitivity. A cross-sectional sample of 107 MMT patients were studied using ToM (Reading the Mind in the Eyes [RMET]), empathy (Interpersonal Reactivity Index [IRI]), Empathy Quotient Scale for Adults [EQ60]), and Pain Empathy [PE task]). Pain threshold and supra-threshold were measured using visual analog scale response to algometer's pressure. Catastrophizing and Montreal Cognitive Assessment (MoCA) questionnaires were administered, and drug use was monitored in urine drug screens. Normal ToM (RMET ≥ 22) prevalence was 27% of patients who were characterized by being younger, having higher cognitive, empathy, and pain empathy scores, and fewer substances in urine drug screens. They experienced less catastrophizing, and yet additional pain components were comparable. MMT patients with normal ToM showed high empathy, but were not dependent on pain variables which differed from previous reports by healthy subjects.